Gestão, trabalho e adoecimento docente: caminhos e descaminhos na Fundação Escola Bosque - REIS, Maria Izabel Alves dos (2009)
The present research explored the theme management, work and teachers’ health. The objective of this study was to analyze the possible relationship between work and teachers’ health and the changes in the management of Escola Bosque, in the period of 1996 to 2006. On this way, the research proposed specifically: a) analyze the relationship established between teachers and pedagogical management; b) investigate if the changes in the school’s management contributed with the sickness/distancement of the teachers; c) analyze the existence of politicy of attendiment to teachers’ health included by the Municipal Secretary of Education. To reach these objectives, I realized a study of event. From this research the essay was organized in three parts. In the first, I make a bibliografy analysis around the sickness of teachers, looking for interconnection with the educational reforms in the years of 1990 and its relationships with the changes of conceptions of education, management and teachers’ work, in front of economic and social politicy’s reconfigurations; In the second part, I present the research’s locus, in which we show the main happenings that turned possible the conception and the build of Escola Bosque, and the fundaments and pedagogical politicy project, where the teachers’ work is guided having, the PFL’s government management. In the third part, I show the different programs in the educational area, developed by municipal governments, in two managements of PT (1997 to 2004), and the two initial years of PTB’s management; showing repercussion on work and Escola Bosque’s management, the precocious relationship in the interior of the researched school, the conceptions of the teachers’ work and consequences to workers’ health. The conclusion of this research, is that can exist a connection between the management of education and the form how it presents itself on Escola Bosque and the distancement and sickness of teachers of this institution.